Chronic Liver Failure Mechanisms and Management - Ginès, Pere; Kamath, Patrick S.; Arroyo, Vicente (Clinical Gastroenterology,, 2011)
Chronic liver failure is a frequent condition in clinical practice that encompasses all manifestations of patients with end-stage liver diseases. Chronic liver failure is a multiorgan syndrome that affects the liver, kidneys, brain, heart, lungs, adrenal glands, and vascular, coagulation, and immune systems. Chronic Liver Failure: Mechanisms and Management covers for the first time all aspects of chronic liver failure in a single book, from pathogenesis to current management. Each chapter is written by a worldwide known expert in their area and all provide the latest state-of-the-art knowledge. This volume is specifically designed to provide answers to clinical questions to all doctors dealing with patients with liver diseases, not only clinical gastroenterologists and hepatologists, but also to internists, nephrologists, intensive care physicians, and transplant surgeons.